Determinants of reactive agility performance in table tennis players - Hornikova, H. (Studia Sportiva, 2022)
BACKGROUND: Table tennis is considered as a reaction sport, in which reaction speed is the key factor of sports performance. However, in addition to the quality of sensory (or cognitive) functions, it also requires a rapid motor response. Reactive agility is one of the most important qualities of table tennis performance. It comprises both sensory and motor components. Therefore, the aim of this study was to find the relationship between reactive agility performance and reaction speed (sensory part), sprint and change of direction speed, and muscle strength parameters (motor part) and thus to identify determinants of reactive agility in table tennis players.